ATTRACTING FOREIGN INVESTMENT AND MODERNIZATION PROCESSES IN THE CONTEXT OF THE DIGITAL ECONOMY (American Journal of Business Management, Economics and Banking, 2026)
This article examines the improvement of investment policy in Uzbekistan, economic modernization, and the development of the digital economy. It highlights the importance of attracting foreign investments, improving the investment climate, and their impact on economic growth. The study also analyzes the efficient use of investment resources, industrial development, and the application of international experience. As a result, scientific conclusions are formulated to enhance national economic competitiveness and ensure sustainable development.